Modification of the growth of iron on Ag(111) by predeposited organic monolayers - Buchner, Florian; Kellner, Ina; Steinrück, Hans-Peter; Marbach, Hubertus (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2009)
We study the modification of the growth behaviour of iron on Ag(l11) by preadsorbed monolayers of 2H-phthalocyanine (2HPc) and 2H-tetraphenylporphyrin (2HTPP) by scanning tunneling microscopy, upon Fe deposition in ultra-high vacuum at room temperature. The growth of iron on clean Ag(111) follows the scheme expected from reports of similar systems: For low coverages (up to-0.3 ML) an almost exclusive agglomeration of iron clusters at step edges occurs, which continue to grow in a dendritic fashion at higher coverages. Upon deposition onto Ag(l11) precovered with monolayers of 2HTPP and 2HPc, at coverages up to 0.037 ML no growth of Fe islands but complete metalation, i.e., incorporation of the Fe atoms in the macrocyle of the preadsorbed molecules is found. For higher amounts of deposited Fe (0.037 < 0 < 0.30 ML), the formation of Fe islands is observed, which occurs differently for 2HPC and 2HTPP. While on 2HTPP two-dimensional islands are formed presumably underneath a FeTPP monolayer, for 2HPc the Fe growth is dominated by the formation of small 3D clusters within a FePc monolayer. At 0 = 2.0 ML, both systems exhibit small three dimensional Fe islands. These results are discussed considering different aspects like the molecular conformation of FeTPP and FePc on Ag(111) and the diffusional properties of Fe on the clean and modified substrate. © by Oldenbourg Wissenschaftsverlag.